Asked by  | 2nd Aug, 2008, 07:48: AM

Expert Answer:

given a, x1, x2 ,b are in ap ,so there are total 4numbers.

so a4th = a1+(n-1)d    where a1=a , n=4 and d=(x2-x1)

therefore b=a+3(x2-x1)

=> (x2-x1) = (b-a)/3       simillarly given a , y1, y2, y3, b are in ap ,so we will get (y2-y1) = (b-a)/4 

therefore , (y2-y1) / (x2-x1)  = (b-a)/4 / (b-a)/3  = 3/4    answer

Answered by  | 5th Aug, 2008, 11:17: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.